Innovative Exploration and Practice of Archives Collection Automation - Liu, Zhe (European Journal of AI, Computing & Informatics, 2025)
As a fundamental part of archives management, the efficiency and quality of archives collection directly affect the utilization of archival resources. Currently, China’s archives collection work is in a critical period of transition from traditional models to digitalization, facing multiple challenges such as technical bottlenecks, outdated concepts, and institutional obstacles. This paper systematically analyzes the current situation and existing problems of archives collection work from four dimensions: technical dilemmas in collection methods, backwardness in management concepts, innovative explorations in grassroots practice, and prospective development paths. It also proposes practical automation solutions for archives collection, providing references for promoting high-quality development of archival undertakings.